HUBUNGAN DUKUNGAN KELUARGA DAN KEPATUHAN REHABILITASI DENGAN KEMANDIRIAN PASIEN PASCA STROKE - Abyan Shafly Nur Firdaus; Harmayetty Harmayetty; Lailatun Ni’mah (Universitas Airlangga, 2020)
Introduction: Families who do not support patients can influence the level of rehabilitation adherence, which in turn will reduce the level of independence of patients after stroke. The purpose of the study was to explain the relationship between family support and rehabilitation adherence with the independence of stroke patients. Methods: This study used a cross-sectional type with a sample size of 73 post-stroke patients out of a total of 126 people. Samples were taken by consecutive sampling technique. The independent variable is the level of family support and the level of rehabilitation compliance. The dependent variable is the level of independence of patients after stroke. The research data obtained were analyzed with Spearman's Rho α ≤0.05. Results and Analysis: There was a relationship between family support and the independence of post-stroke patients with a value of α≤0.05, p = 0.001 and r = 0.384. There is a relationship between rehabilitation adherence with the independence of post-stroke patients with a value of α≤0.05, p = 0.000 and r = 0.473. Conclusion: Family support and good rehabilitation adherence do not affect post-stroke patients with severe degrees of disability and cognitive changes.